Frequency and appearance of hemosiderin depositions after aneurysmal subarachnoid hemorrhage treated by endovascular therapy - Falter, Bernhard; Wiesmann, Martin; Freiherr, Jessica; Nikoubashman, Omid; Mull, Michael (Neuroradiology, 2015)
It is still unclear how often subarachnoid hemorrhage (SAH) leads to chronic hemosiderin depositions. In this study, we aimed to determine the frequency of chronic hemosiderin depositions after aneurysmal SAH in patients who did not undergo surgery. Furthermore, we analyzed typical MRI patterns of chronic SAH and sought to obtain information on the temporal course of MRI signal changes.We retrospectively analyzed 90 patients who had undergone endovascular treatment for acute aneurysmal SAH. In all patients, initial CT studies and at least one T2*-weighted MRI obtained 6 months or later after SAH were analyzed for the presence and anatomical distribution of SAH or chronic hemosiderin depositions. In total, 185 T2*-weighted MRI studies obtained between 2 days and 148 months after SAH were evaluated (mean follow-up 30.2 months).On MRI studies obtained later than 6 months after SAH, subpial hemosiderin depositions were found in 50 patients (55.5 %). Most frequent localizations were the parenchyma adjacent to the frontal and parietal sulci and the insular cisterns. While the appearance of hemosiderin depositions was dynamic within the first 3 months, no changes were found during subsequent follow-up. MR signal changes were not only conclusive with subarachnoid hemosiderin depositions but in many cases also resembled those that have been associated with cortical hemosiderosis.T2*-weighted MRI is an effective means of diagnosing prior SAH. Our study suggests that chronic hemosiderin depositions can be found in a considerable number of patients after a single event of subarachnoid hemorrhage.
Keywords: Hemosiderin; Endovascular therapy; T2*w magnetic resonance imaging; Subarachnoid hemorrhage; Aneurysm